Fluid boundaries : forming and transforming identity in Nepal - Fisher, William F., 1951- (Columbia University Press, 2001)
Examining the relationship between societal practice, historical processes, and culture in a Nepali society, this book tells the story of the Thakali's search for identity and their efforts to clarify and represent their culture and history.
Keywords: Thakali (Nepalese people) -- Ethnic identity.; Thakali (Nepalese people) -- Social life and customs.; Thakali (Peuple du Népal) -- Identité ethnique.; Thakali (Peuple du Népal) -- Mœurs et coutumes.; SOCIAL SCIENCE -- Anthropology -- Cultural.; SOCIAL SCIENCE -- Discrimination & Race Relations.; SOCIAL SCIENCE -- Minority Studies.; SOCIAL SCIENCE -- Anthropology -- General.; Thakali.; Etnisch bewustzijn.; Ethnische Identität.; Soziale Wirklichkeit.